Pengaruh kompensasi Finansial dan Gaya Kepemimpinan terhadap Kepuasan Kerja Karyawan dan Organizational Citizenship Behavior (OCB) pada Hotel Alit's Beach Bali - Angelina, Angelina; Subudi, Made (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
Job satisfaction and OCB will reflect the positive attitude of each individual in completing tasks and loyalty to the company. This study focused on Alit's Beach Hotel Bali, Sanur. Total samples are 70 employees without leaders, using probability sampling methods. The study used path analysis model. The test results showed thatthe financial compensation affect significantlyon employee job satisfaction, significant effect of leadership style on employee job satisfaction, financial compensation significant effect on OCB, and leadership style significantly influence OCB and job satisfaction have a significant effect on OCB. Keywords: financial compensation, leadership style, job satisfaction, and organizational citizenship behavior (OCB)
Keywords: financial compensation, leadership style, job satisfaction, organizational citizenship behavior (OCB)